Implementasi Model Pembelajaran Problem Based Learning Pada Pelajaran Ilmu Pengetahuan Alam (IPA) Kelas IV MI Muhammadiyah Madureso - Fitriyani, Hajrul; Maryanto, Maryanto (IAINU Kebumen, 2025)
This study aims to determine the implementation of the PBL learning model for the material properties of the image in the mirror and to find out whether the Problem-Based Learning (PBL) model affects the level of student understanding. This study uses Mix Methods research, which is a combination of qualitative and quantitative research. The design in this study uses an exploratory sequential design. Collecting data using observation techniques, interviews, and written tests. The data analysis technique used is qualitative data analysis techniques including: data condensation, data presentation, and conclusion. While the quantitative data analysis technique is the independent sample t-test type t-test. The results showed that the implementation of the PBL learning model for the material on the properties of the image in the mirror is as follows: 1) In the planning stage of the Problem-Based Learning model, the material for the properties of the image in the mirror consists of preparing teaching material, preparing a lesson plan (RPP). ) as well as preparing evaluation tools and learning media. According to the author, the syntax for implementing the problem-based learning model includes 1) student orientation towards problems, 2) student organizations towards learning, 3) conducting independent and group investigations, 4) developing and presenting work, and 5) analyzing and evaluating the problem-solving process. Based on the student learning outcomes assessment activities, it consists of 1) the affective aspect has gone well in the spiritual and social assessment of students, 2) the cognitive aspect, there is an increase in understanding after the implementation of the Problem-Based Learning model and the average completion in natural science subjects -the nature of the image in the mirror, and 3) the psychomotor aspect in terms of problem-solving and practice tests identifying the characteristics of the image in the mirror is done well. The Problem-Based Learning model affects the level of students' understanding of science lesson material about the properties of the image in the mirror, this is proven based on the Two-Sample T-Test using Excel software.